Prevalence of Visceral Schistosomosis in Buffaloes Slaughtered at Mumbai - Kubde, Mukta G; Palampalle, Hirachand Y; Pednekar, Riddhi P (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was carried out to record the prevalence of visceral schistosomes in buffaloes slaughtered at Deonar abattoir from March 2022 to February 2023. A total of 592 mesenteries and 368 intestinal contents of slaughtered buffaloes were randomly screened for the presence of schistosomes and gastrointestinal parasites. Out of 592 mesenteries, 95 animals (16.05%) were positive for Schistosoma spp. while intestinal content of 38 animals (10.32%) was positive for the presence of GI parasites. Amphistomes (75.67%) was the most predominant GI parasite in the intestinal content followed by Strongyle spp. (5.40%), coccidia (5.40%), Capillaria spp. (2.70%), S. spindale (2.70%), Fasciola spp. (2.70%) and Trichuris spp. (2.70%). Mixed infection was reported in 5.04 % animals. Highest prevalence of gastrointestinal parasites was recorded in summer (43.24%) followed by monsoon (37.83%) and winter (18.91%) with peak prevalence in month of October (16.67%) and lowest in March (4.17%). The prevalence of blood flukes was highest in winter (45.24%) followed by summer (34.73%) and monsoon (20.00%) with a peak in month of February (23.53%) and lowest in March (2.08%). Mild intensity of infection was predominant in 36.84 % buffaloes while 5.26% buffaloes showed moderate intensity of infection. Schistosomes recovered from the mesenteries were identified as Schistsoma spindale based on their morphometry with male flukes predominating the females. Slaughtered buffaloes belonging to Thane, Mumbai and Satara district were found positive with highest incidence from Thane (20.48%) followed by Mumbai (16.47%) and Satara (11.30%) District of Maharashtra. Considering the prevalence rate of visceral schistosomosis, we can conclude that animals and human in these regions are sub-clinically at risk. The conventional diagnostic method fails to detect the active infection in animals and human. Hence, advanced molecular and serological techniques should be employed to detect the infection in farm animals so that effective control strategies can be implemented.